Maria sebagai "role model" bagi wanita Kristen masa kini berdasarkan kitab Injil Matius dan Lukas - Frida Laurencia; Grace Son Nassa (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2021)
This research highlights the profile of the life of Mary, the mother of Jesus, which is studied based on the Bible, especially the Gospels of Matthew and Luke. In this research, we will cover five aspects of Mary's life: her spiritual life, character, morality, mentality, and role as a wife and a mother. The goal of this research is for Christian women living today to understand these five perspectives of Mary's profile on how to serve their husbands and to set an example for the children God has entrusted to them. This research uses a qualitative approach with the method of literature. The results of the research shows that Mary’s spiritual life, character, mentality, morality, and her role as wife and mother are biblical according to the word of God. Thus, the values ​​of Mary's life are still relevant to be implemented into the daily lives of today's Christian women.